Does photobiomodulation therapy improve the postoperative outcomes of tonsillectomy? A systematic review and meta-analysis: PBMT in the postoperative of tonsillectomy - de Arruda, José Alcides Almeida; Callou Sampaio, Gerhilde; Velasco Pondé de Sena, Ana Carolina; Frenzel Schuch, Lauren; Pereira Ribeiro, Jaziel; Domingues Martins, Manoela; Aparecida Silva, TarcÃlia; Alves Mesquita, Ricardo; Guimarães Abreu, Lucas (Journal of Lasers in Medical Sciences, 2022)
Introduction: Postoperative management of patients undergoing tonsillectomy is challenging. Photobiomodulation therapy (PBMT) has emerged as a new tool providing therapeutic benefits. However, the contribution of PBMT to the postoperative outcomes of tonsillectomy is still undefined. This systematic review and meta-analysis evaluated the published literature addressing the effects of PBMT on post-tonsillectomy. Methods: Searches in Scopus, PubMed/MEDLINE, Embase, Web of Science, Cochrane Library, and grey literature were carried out for the identification of randomized controlled trials reported up to August/2021. The risk of bias with the Cochrane Collaboration tool and meta-analysis was performed. Outcomes were assessed with the Kaplan-Meier method and the log-rank test. Results: A total of 1183 articles were retrieved, of which only two were included for qualitative and quantitative analysis. The wavelengths were 685 nm and 980 nm with energy density set at 4 J/cm². The mandibular angle and the surgical wound were the sites of laser irradiation. Individuals who had not undergone PBMT after tonsillectomy were more likely to report pain and odynophagia in the first 24 hours after surgery than individuals who had undergone PBMT after tonsillectomy (P<0.001). Children who received PBMT after tonsillectomy were equally affected by pain and odynophagia in the first seven days after surgery compared to children who had not undergone PBMT after tonsillectomy (P>0.05). However, both studies found a significant association of PBMT with reduced analgesic consumption. Conclusion: Although PBMT seems promising for the management of individuals undergoing tonsillectomy, a limited number of studies are available in the literature. Doi:10.34172/jlms.2022.07.